Spectrum of White Light During Incubation: Warm vs Cool White LED Lighting - Archer , Gregory S. (International Journal of Poultry Science, 2016)
Objective: Commercially chicken eggs are incubated in darkness, though naturally they would receive light exposure. Light has been shown to affect hatchability and post hatch development. Methodology: To determine if there is an effect of exposing embryos to light of warm (3900 K) or cool (5500 K), we incubated broiler chicken eggs (n = 3096) under either no light (Dark), warm LED (Warm) or cool LED (Cool) light; the light level was 550 lux. Dark eggs had lower hatchability (Dark 80.1±1.5%, warm 86.5±1.3% p = 0.01, cool 84.9±1.0% p = 0.03), less top quality chicks (Dark 56.6±4.7%, warm 82.1±1.7% p = 0.001, cool 79.0±3.0% p = 0.002), more pipped unhatched eggs (Dark 3.3±1.2%, warm 1.3±0.5% p = 0.01, cool 1.3±0.4% p = 0.03) and more chicks with unhealed navels (Dark 40.8±5.2%, warm 15.5±3.2% p = 0.002, cool 19.1±2.5% p = 0.003) when compared to either warm or cool. Results: A subset of each treatment (n = 160 chicks per treatment) was grown for 14 days. Stress susceptibility was assessed using a composite asymmetry score determined by middle toe length and metatarsal length and width. Dark chicks had a higher level of composite physical asymmetry (1.52±0.09 mm) than did warm (1.17±0.07 mm, p = 0.004) and cool (1.19±0.09 mm, p = 0.006) broilers. Dark chicks were more fearful than warm and cool as they vocalized more (118.5±8.5 vocal/3 min) than warm and cool (87.1±7.4 and 92.4±9.0 vocal/3 min, respectively; p = 0.001 and p = 0.03). There were no differences observed in 14 days growth or FCR (p>0.05). Conclusion: The results indicate that LED light stimulation of chickens during embryogenesis results in increased hatchability, improved chick quality and has long-term effects on fear responses and stress susceptibility, furthermore they also indicate that warm vs cool light was not a factor.